Comorbidities associated with higher von Willebrand factor (VWF) levels may explain the age‐related increase of VWF in von Willebrand disease. (16th May 2018) - Atiq, Ferdows; Meijer, Karina; Eikenboom, Jeroen; Fijnvandraat, Karin; Mauser‐Bunschoten, Eveline P.; van Galen, Karin P. M.; Nijziel, Marten R.; Ypma, Paula F.; de Meris, Joke; Laros‐van Gorkom, Britta A. P.; van der Bom, Johanna G.; de Maat, Moniek P.; et al.
Summary: Some comorbidities, such as hypertension, are associated with higher von Willebrand factor (VWF) levels in the general population. No studies have been conducted to assess this association in patients with von Willebrand disease (VWD). Therefore, we studied this association in patients with type 1 ( n = 333) and type 2 ( n = 203) VWD from the 'WiN" study. VWF antigen (VWF:Ag) was higher in type 1 VWD patients with hypertension [difference: 0·23 iu/ml, 95% confidence interval (CI): 0·11–0·35], diabetes mellitus (0·11 iu/ml, 95% CI: −0·02 to 0·23), cancer (0·14 iu/ml, 95% CI: 0·03–0·25) and thyroid dysfunction (0·14 iu/ml, 95% CI: 0·03–0·26) than in patients without these comorbidities (all corrected for age, sex and blood group). Similar results were observed for VWF collagen binding capacity (VWF:CB), VWF activity as measured by the VWF monoclonal antibody assay (VWF:Ab) and factor VIII (FVIII) coagulant activity (FVIII:C). In type 1 VWD, age was associated with higher VWF:Ag (0·03 iu/ml; 95% CI: 0·01–0·04), VWF:CB (0·02 iu/ml; 95% CI: 0·00–0·04), VWF:Ab (0·04 iu/ml; 95% CI: 0·02–0·06) and FVIII:C (0·03 iu/ml; 95% CI: 0·01–0·06) per decade increase. After adjustment for relevant comorbidities, these associations were no longer significant. Despite the higher VWF and FVIII levels, type 1 VWD patients with comorbidities had more bleeding episodes, particularly during surgery. There was no association between comorbidities and VWF/FVIII levels or bleeding phenotype in type 2 VWD patients. In conclusion, comorbidities are associated with higher VWF and FVIII levels in type 1 VWD and may explain the age‐related increase of VWF and FVIII levels.